2020
DOI: 10.1021/acssuschemeng.9b05450
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Earthworms to Enhance Decaying of Biodegradable Plastics

Abstract: Biosolid application, wastewater irrigation, and plastic mulching technologies are major sources of plastic pollution in agroecosystems. Microplastics may interact with soil physicochemical properties and organisms and negatively affect plant growth. To alleviate environmental plastic pollution, synthetic and biobased biodegradable polymers are replacing nonbiodegradable polymers, but their biodegradation rate in the field is frequently lower than that estimated from standardized biodegradation testing. Plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 182 publications
(302 reference statements)
0
31
0
Order By: Relevance
“…Farmers who were affiliated with an FVPO obtained 50% off their invoice in replacing plastic mulch and 66% off the replacement of trellising elements [109,110]. This has solved a large portion of the cost overrun [111]. The use of biodegradable plastic, which decomposes naturally [109], or other organic materials (straw, rice husks, etc.)…”
Section: Opportunities For Waste Management and Use Of Plastic By-products By The Different Agents Involved: Inclusion In The Cementioning
confidence: 99%
“…Farmers who were affiliated with an FVPO obtained 50% off their invoice in replacing plastic mulch and 66% off the replacement of trellising elements [109,110]. This has solved a large portion of the cost overrun [111]. The use of biodegradable plastic, which decomposes naturally [109], or other organic materials (straw, rice husks, etc.)…”
Section: Opportunities For Waste Management and Use Of Plastic By-products By The Different Agents Involved: Inclusion In The Cementioning
confidence: 99%
“… 58 Some authors have suggested nanoplastics would be similarly transported, albeit without providing empirical evidence. 60 Considering that initial investigations on microplastics showed increasing transport with decreasing size, 53 it appears reasonable that nanoplastics could be more susceptible to biologically driven transport and, in particular, ingestion/excretion dynamics. However, experimental evidence for nanoplastics uptake by earthworms and biologically mediated transport is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradation (degradation by using microorganisms/enzymes) of pretreated (grinding/irradiation) plastic is noted to be a potential route to reduce the problems associated with waste plastics 153,154 . It is also noted that earthworms can enhance the degradation of biodegradable plastics in soil 155 . Consequently, innovative pretreatment coupled with technological advances could enhance the degradability of waste plastics.…”
Section: Terrestrial Ecosystemmentioning
confidence: 99%